Moçambique, 30 anos de independência - Bouene, Felizardo (Africana Studia, 2020)
Mozambique became a Portuguese colony after the Conference of Berlin in 1884-85. The resistance manifested until then was renewed with the struggle for freedom led by the Frente de Libertação de Moçambique (FRELIMO), from 1964 on. Once the independence was achieved, in 25th June 1975, Mozambique had essentially two political periods: the revolutionary period and civil war (from 1975 to 1992) and the national reconciliation period (from 1992 on). During the independence Mozambique advanced mainly in the domains of education and health. The signing of the Peace Settlement created the necessary conditions for the trust of the economic agents.